SINTESIS MANGANESE FERRITE DENGAN METODE MECHANICAL ALLOYING DARI BIJIH MANGAN ALAM - syamsul bahtiar; Imam Wierawansyah Eltara; Fauzi Widyawati; Syamsul Hidayat (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2022)
One of the largest natural resources of manganese ore in Indonesia is located in the Regency of Sumbawa Besar and has high manganese content. Manganese ore can be used to form manganese ferrite compounds. The synthesis of manganese ferrite (MnFe2O3) consists of an alloy of manganese ore (MnO2) and hematite (Fe2O3) obtained from mill scale steel production waste. The two particles are then combined by the mechanical alloying method. Manganese ore is first calcined at temperature variations of 400oC, 500oC, and 600oC. The mechanical alloying process of manganese and hematite ore by varying the amount of manganese ore 1: 1, 1: 2, 1: 3, 1: 4. Furthermore, the mixture of particles was calcined at a temperature of 1100oC for 3 hours to obtain homogeneous manganese ferrite. Initial XRD characterization obtained manganese ore in the form of pyrochroite (Mn(OH)2) and after calcination at a temperature of 500oC pyrolusite (MnO2) was formed. The final results of XRD and XRF characterization showed that the addition of MnO2 to Fe2O3 produced manganese ferrite bixbite (MnFe2O3) with a formation intensity of 70%. Dominant MnFeO3 phase at a 4: 1 ratio. The more MnO2 added to Fe2O3, the more manganese ferrite bixbite phases are formed.